PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMILIHAN SEKOLAH PADA SMP RAKYAT SEI GLUGUR - Syainatun Purnawati; Fahmi Ashari S. Sihaloho (Jurnal Utilitas, 2020)
This study aimed to describe the effect of the marketing mixs on school selection decisions at Sei Glugur Rakyat Junior High School including product, price, and place elements. This study used a descriptive research design using a questionnaire instrument. The data research data of product, price, and place effect scores were processed using statistical analysis to prove the alternative hypothesis that there was a significant effect of product, price, and place on school selection decisions. The results showed that there was a significant effect of product, price, and place influence on school selection decisions.